Significado atribuidos por enfermeiros à assistênvcia que prestam a indivíduos em situação prisional - Apolinario, Fernando Henrique [UNESP] (2013)
This study is about the significance of the assistance practices of the nurses who work in the penitentiary system of the Western region of the State of São Paulo, attending the incarcerated. The objective of this research is to characterize the units and identify the perceptions and the significances given to the nurses who work in the prison system by taking care of the prison inmates in closed system units. The methodological approach used to order and to analyse the obtained data by semistructured interviews was the Collective Subject Discourse. The “QualiQuantSoft’ software was used in this methodological process. The subjects of this research were the nurses that work at the above-mentioned service. With regard to the practice of nursing, it was possible to draw a picture marked by conflict imposed in hierarchical relationships, both formal and informal, that govern the routines at the prison units, especially the sectors of health and safety. Many difficulties for the accomplishing of the assistance were encountered: lack of a doctor, overcrowding, physical environments inappropriate for the attending of the subjects, insecurity, fear of working in the prison unit and, finally, the difficulty of making a reference and counter-reference according to the precept of integrality. Despite this difficulty, the nurse’s vision is one of a caregiver, with great meaning for his/her practices, because the feeling of empathy and the solidarity with those who are deprived of their liberty and are sick is quite evidenced. The nurse disregards the social condition of the detainee, identifying him as a human being in need of healthcare. The main ethical dilemmas experienced everyday by the nurses, according to reports, were related to the loss of autonomy in the nurses’ private competences, neglect in the care of the individual deprived of liberty in some municipalities and health units, and the impositions of assignments ...